2021
DOI: 10.21037/tlcr-20-894
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in older patients with wild-type epidermal growth factor receptor advanced non-small cell lung cancer: a multicenter retrospective study

Abstract: Background: Over 40% Japanese patients with lung cancer are above 75 years of age. A specific strategy to treat such older patients is necessary because most trials exclude older patients with poor physical health.Herein, we aimed to identify predictive factors associated with overall survival (OS) in older patients by evaluating patient backgrounds and laboratory data before the start of treatment.Methods: This multicenter retrospective medical chart review study was conducted at three Japanese institutions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…[18] Another population-based study in lung cancer patients 80 years or older showed inferior outcomes due to lower treatment rates. [10,11] Tas et al reported poor outcomes of the elderly patients (≥60 years). [5] Our findings revealed a tendency for shorter overall survival in geriatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[18] Another population-based study in lung cancer patients 80 years or older showed inferior outcomes due to lower treatment rates. [10,11] Tas et al reported poor outcomes of the elderly patients (≥60 years). [5] Our findings revealed a tendency for shorter overall survival in geriatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found decreased survival rates in the elderly patients when the cut-off values of age starting from 60 years and over were used. [5,10,11,15] In advanced NSCLC patients with over 70 years has not been studied in detail.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The main reasons for receiving BSC were poor PS, advanced age together with dementia and the patients’ wish. Interestingly, single agent chemotherapy was the selected treatment in the majority of cases receiving an active treatment [ 14 ]. Similar data were reported in a retrospective analysis about the reasons for choosing BSC as initial treatment.…”
Section: Discussionmentioning
confidence: 99%